2021
DOI: 10.1051/e3sconf/202126403002
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic parameters in the area of the main dam intake structure of the river

Abstract: The article presents the study results of changes in flow hydraulic parameters and morphometric elements of the river in the area of the main dam intake structure. A model for studying the direction of flow and other parameters of the flow in the area of the main structure for obtaining water from the Amudarya without a dam has been developed. A functional graph of the depth dependence of the expenditure on the study object was obtained. Graphs of the functional dependence of the diurnal cross-section of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…When installing the model, the width of the tunnel tray was maintained using templates installed in pairs along its entire length [15][16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…When installing the model, the width of the tunnel tray was maintained using templates installed in pairs along its entire length [15][16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…When testing soil pumps [13][14][15][16], it was found that parts made of electrocorundum on an epoxy-phenol-formaldehyde binder, compared with parts made of wear-resistant cast iron, increased the service life of pumps by 3-8 times. But the use of wear-resistant polymeric materials for the manufacture and coating of pump parts has not been widely used in practice due to the following reasons [17,18]: 1) polymer compositions do not provide satisfactory wear resistance at high flow rates; 2) the rough surface of polymer coatings creates additional hydraulic resistance and degrades hydraulic efficiency; 3) the quality of polymer coatings is highly dependent on strict adherence to the application technology.…”
Section: Fig 2 the Dependence Of The Intensity Of Wear Of The Impelle...mentioning
confidence: 99%
“…The impact of water diverted for irrigation is particularly strong on the discharges of the Logar River, the upper Kabul River, and the Gorband River (a tributary of the Panjshir). Traditional forms of irrigation are used so firmly and for a long time on all lands practically suitable for irrigation in river valleys that they were obtained without considering irretrievable water losses [14][15][16][17][18][19][20][21][22].…”
Section: Land Cover Informationmentioning
confidence: 99%